Model Development of Nursing Student Loyalty in Politeknik of Health - Hammad Hammad; Nursalam Nursalam; Ninuk Dian Kurniawati (Jurnal Ners, 2013)
Introduction: Loyalty of nursing student is an important factor that nursing education should pay attention in order to compete with other nursing educations; involved by perceived value, expectation, and quality assurance in nursing higher education. The purpose of this study was to develop a loyalty model of nursing student in nursing higher education.Methods: This study was an explanatory research with cross sectional approach. Population were nursing student in Poltekkes Banjarmasin, with 112 samples which is selected by proportional random sampling. Data was collected by giving questionnaire and analyzed by partial least square.Result: Result of this study indicates that was an effect of costumer expectation on quality assurance in nursing higher education, there was effect of costumer expectation on perceived value in nursing student, there was an effect of customer expectation on student satisfaction (4) there was effect of quality assurance in nursing higher education, there wasn’t any affect of quality assurance in nursing higher education on student satisfaction, there was effect of perceived value in nursing student on student satisfaction, there was effect of student satisfaction on student loyalty. Conclusion: Overall result of this research were, student loyalty in nursing higher education developed by student satisfaction. Student satisfaction formed by perceived value. Perceived value developed from two aspects quality assurance, and student expectation, quality assurance of higher education wasn’t directly effect to student sasfaction. However, indirectly effect through student perceived value. Student satisfaction in nursing higher education was stronger effect than any other variable in this loyalty model. Loyalty model in this research can be use for improvement student loyalty on health education that focused on improvement student satisfaction without deny the other aspect. Further research is needed to analyze word of mouth effect on student loyalty.